Development of an Expert System for the Analysis of Technological Disasters in Malaysia - Mohamed Shaluf, Ibrahim (2004)
Malaysia has experienced several technological disasters in the last decade due to the operation of Major Hazard Installations (MHIs). Currently Malaysia operates 177 MHIs and Malaysia is witnessing continuous growth in MHIs. The number of MHIs increases at an average rate of 19 installations per year. This study reviews and analyses technological disasters (TD), which has occurred in Malaysia. The objectives of this study were to identify factors responsible of technological disasters, a combination of which triggered the technological disasters, to develop a model describing the pre-technological disaster stage, and an Expert System that could be used to aid the management of MHIs to control their installation. To achieve these objectives, a review of previous studies on disaster management in Malaysia was carried out together with an analysis of the technological disaster inquiry reports. A field survey and interview of the domain experts was also done.Information research accidents, which occurred in Malaysia, was obtained from several sources. It has been found that Malaysia has experienced 28 disasters during the period 1968 to 2002. The disasters have resulted in 1,635 fatalities, 1,929 injuries, and caused severe damage to properties. Seven technological disasters have resulted in 104 fatalities and 201 injuries. Four technological disaster inquiry reports have been reviewed in detail. This study shows that the factors, which contributed to the technological disasters in Malaysia, were mainly due to Social, Technical, Organizational, Operational, Investigational and Defences errors. It has been found from international experience that there are only a few models describing the disaster precondition stage. This study has produced a pre- technological disaster model. The model is called the Ibrahim-Razi model for technological disasters. This model describes the sequence of development of the pre- disaster stage in eight phases. A field survey was carried out through a questionnaire. The targeted respondents were the Safety, Health and Environment Managers at the MHIs. Domain experts interviews were also conducted. Descriptive analysis, Pearson correlation, and regression analysis were used for the data analysis. CLIPS (C Language Integrated Production System) was used as a medium for the development of Technological Emergencies Expert System (TEES). The TEES is versatile, portable, reliable, and applicable to other emergencies applications. This study provides a tool as an aid for the Safety Managers, as well as the DOSH in decision making and to assess the state of the MHIs.